Cover Image, Volume 19, Issue 12. Issue 12 (6th November 2017) - Dassau, Eyal; Renard, Eric; Place, Jérôme; Farret, Anne; Pelletier, Marie‐José; Lee, Justin; Huyett, Lauren M.; Chakrabarty, Ankush; Doyle, Francis J.; Zisser, Howard C.
Abstract : The cover image, by Eyal Dassau et al., is based on the Original Article Intraperitoneal insulin delivery provides superior glycaemic regulation to subcutaneous insulin delivery in model predictive control‐based fully‐automated artificial pancreas in patients with type 1 diabetes: a pilot study, DOI: 10.1111/dom.12999 . Design Credit: Harvard University. Abstract : The cover image, by Eyal Dassau et al., is based on the Original Article Intraperitoneal insulin delivery provides superior glycaemic regulation to subcutaneous insulin delivery in model predictive control‐based fully‐automated artificial pancreas in patients with type 1 diabetes: a pilot study, DOI: 10.1111/dom.12999 . Design Credit: Harvard University.